Fibroblast growth factor 17 and bone morphogenetic protein 15 enhance cumulus expansion and improve quality of in vitro-produced embryos in cattle - Machado, Mariana Fernandes [UNESP]; Caixeta, Ester Siqueira [UNESP]; Sudiman, Jaqueline; Gilchrist, Robert B.; Thompson, Jeremy G.; Lima, Paula Fernanda [UNESP]; Price, Christopher A.; Buratini, Jose [UNESP] (Elsevier B.V., 2015)
Bone morphogenetic protein 15 (BMP15) and members of the fibroblast growth factor (FGF) family are expressed by the oocyte and are involved in the control of cumulus cell function. We tested the hypothesis that FGF17, alone or combined with BMP15 in the maturation medium, enhances cumulus expansion, meiosis progression, embryonic development, and expression of mRNA encoding key genes regulating expansion (prostaglandin-endoperoxide synthase 2 [PTGS2], hyaluronan synthase 2 [HAS2], tumor necrosis factor-stimulated gene 6 [TNFAIP6], and pentraxin 3 [PTX3]) and markers of oocyte developmental competence (phosphofructokinase [PFKP], gremlin [GREM1], versican [VCAN], and the genomic progesterone receptor [nPR]) in cumulus cells. Fibroblast growth factor 17 and BMP15 increased the percentage of fully expanded cumulus-oocyte complexes (COCs), but there was no additive effect when both were combined. Neither FGF17 nor BMP15 altered the percentage of oocytes reaching meiosis II at the end of COC culture or cleavage and blastocyst rates after IVF. However, embryo quality, as assessed by the number of cells in the inner cell mass, was improved by the combination of FGF17 with BMP15. Fibroblast growth factor 17 alone did not alter gene expression in cumulus cells at the end of IVM, whereas BMP15 increased PTGS2 and PTX3 mRNA levels. The combination of FGF17 and BMP15 increased nPR mRNA abundance in cumulus cells but did not change the expression of other markers of developmental competence. This study provides novel evidence that FGF17 enhances cumulus expansion in bovine COCs submitted to IVM and that the supplementation of the IVM medium with FGF17 and BMP15 may improve embryo quality.
Keywords: Fibroblast growth factor 17; Bone morphogenetic protein15; Oocyte maturation; Cumulus expansion; Embryo quality